2020
DOI: 10.1080/09537104.2020.1863938
|View full text |Cite
|
Sign up to set email alerts
|

Is the endogenous ligand for PEAR1 a proteoglycan: clues from the sea

Abstract: Platelet Endothelial Aggregation Receptor 1 (PEAR1) is an orphan receptor of unknown function which mediates powerful activation of platelets and endothelial cells in response to crosslinking by antibodies and sulfated polysaccharides belonging to the dextran and fucoidan families. PEAR1 is a single transmembrane protein composed of 15 epidermal growth factor-like repeat sequences and with a conserved binding motif, YXXM, which when phosphorylated binds to phosphoinositide 3-kinase (PI3K). The 13 th of the rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Previous studies have reported an interaction between PEAR1 and High affinity immunoglobulin epsilon receptor subunit alpha (FcεRIα) 36 . The differing expression pattern of these two proteins, the inability of monomeric FcεRIα to activate platelets, and the lack of conservation in mouse suggests FcεRIα is not the primary physiological ligand of PEAR1 31 , although pentameric FcεRIα may have a role in PEAR1 signaling 36 . Similarly, the only protein known to interact with SVEP1 is integrin α9β1 55 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported an interaction between PEAR1 and High affinity immunoglobulin epsilon receptor subunit alpha (FcεRIα) 36 . The differing expression pattern of these two proteins, the inability of monomeric FcεRIα to activate platelets, and the lack of conservation in mouse suggests FcεRIα is not the primary physiological ligand of PEAR1 31 , although pentameric FcεRIα may have a role in PEAR1 signaling 36 . Similarly, the only protein known to interact with SVEP1 is integrin α9β1 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies that bind to the extracellular domain (ECD) of PEAR1 (PEAR1ECD) are capable of dimerizing and activating the protein, leading to its association with p85 PI3K and activation of AKT. It is speculated that PEAR1 may be a platelet binding partner 17 , 29 or proteoglycan receptor 31 , but its function in platelets remains poorly understood. In addition, PEAR1 (also known as JEDI or MEGF12) contributes to neoangiogenesis in endothelial cells 32 and glial engulfment 33 35 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current antiplatelet drugs such as aspirin and P2Y 12 receptor antagonists target G protein-coupled receptor (GPCR) regulated pathways but are not effective in all individuals and cause a significant increase in risk of bleeding in some people and this can be life-threatening. The glycoprotein receptors GPVI, CLEC-2 and PEAR1 are considered to be targets for a new class of antithrombotic agents based on mouse models and genome-wide association studies with inhibition predicted to cause less bleeding than current antiplatelet agents [ 1 , 2 ]. These receptors are activated by clustering, and antagonists must therefore overcome the net effect of ligand affinity and avidity for effective inhibition, thus favouring inhibitors with high affinity and a slow off-rate of dissociation.…”
Section: Introductionmentioning
confidence: 99%
“…This includes the GPVI-FcRγ complex and the low affinity immune receptor, FcγRIIA, which signal via an immuno-receptor-tyrosine-based activation motif (ITAM) characterised by two conserved YxxL sequences separated by 6–12 amino acids [ 3 , 4 ]. CLEC-2, on the other hand, signals via a single YxxL known as a hemITAM, and PEAR1 via a single YxxM sequence [ 2 , 5 ]. The binding of the tandem SH2 domains in Syk to phosphorylated ITAM or two hemITAM sequences initiates a signalling cascade that leads to activation of phospholipase C (PLC) γ2.…”
Section: Introductionmentioning
confidence: 99%